Perceptions of Dayak culture and education practitioners on project-based learning in primary education - Eliana Yunitha Seran; Imanuel Sairo Awang; Gabriel Serani; Yayan Adrianova Eka Tuah; Anna Marganingsih (Journal of Education and Learning (EduLearn), 2026)
The implementation of the independent curriculum (IC) in Indonesia requires realizing the Pancasila student profile (PSP) at all education levels, including elementary schools (ES). Project-based learning (PjBL) is a suitable model for achieving PSP but needs reinforcement, particularly in fostering attitude and character values. Integrating the noble values of Dayak culture into PjBL is identified as a relevant approach to strengthen PSP. This study explores the perceptions of Dayak culture actors and primary education stakeholders on implementing PjBL in ES to enhance PSP. Data were collected through semi-structured interviews with 12 key informants and analyzed thematically using NVivo software. Findings are categorized into three aspects: planning, implementation, and evaluation of PjBL. Planning focuses on defining learning outcomes, developing tools, and ensuring student readiness. Implementation involves a 5-step PjBL process integrated with Dayak cultural values, emphasizing honesty, religion, collaboration, kinship, creativity, and independence. Challenges include limited cultural and PjBL literacy, insufficient stakeholder collaboration, and inadequate monitoring during PjBL activities. These issues need addressing to optimize PjBL effectiveness in strengthening PSP.